PENGENALAN DAN PELATIHAN PUBLIC SPEAKING BAGI WARGA PAGUYUBAN PERUMAHAN SERPONG GREEN PARADISE - Riastri Novianita; Cindya Yunita Pratiwi; Amalia Tresna Fadhilah; Bobby Octavia Yuskar (Indonesian Collaboration Journal of Community Services, 2022)
Everyone can certainly speak, but not everyone is able to speak easily and attractively in public. Public speaking is an ability or skill that can be learned. The technique can be easily learned and has become a common thing that many people can do. Maybe for some people who are not used to speak in fornt of the public, it becomes a difficult thing to do.  It happens because someone sometimes feels insecure and doesn't prepare well. The use of public speaking today does not only apply to those who are in college or the realm of education, public speaking applies in any domain, such as in the village, public speaking is used in social gathering events, speeches, or the like. in the religious realm, public speaking is used for religious lectures. Of course, nowadays speaking in public is one of the things that becomes a challenge in personal, social, and professional life. For those who have been introduced to or are used to public speaking, it is easy for him to master the audience, but for some who are not used to speak in front of the public, will find it a stressful and scary thing